Technological approaches to grow-out: a comparative study of pikeperch (Sander lucioperca) culture in three different production systems during the growing season - Kučera, Václav; Pěnka, Tomáš; Malinovskyi, Oleksandr; Kolářová, Jitka; Regenda, Ján; Policar, Tomáš (Frontiers in Marine Science, 2025)
This study compares pikeperch (Sander lucioperca) production in three systems: a recirculating aquaculture system (RAS), an in-pond raceway system (IPRS), and a traditional pond polyculture (POND). Each system was stocked with 1500 juveniles and cultured for 24 weeks. The RAS fish exhibited the most intensive growth, achieving the highest final total length, final body weight, condition factor and specific growth rate, alongside the lowest food conversion ratio (FCR). However, the increased hepatosomatic index, intraperitoneal fat and ammonia levels suggested an increased metabolism. Notably, RAS fish displayed the highest frequency of fin erosion, particularly in the caudal and first and second dorsal fins. The IPRS group exhibited slower growth, higher FCR and higher plasma glucose levels than the other groups. IPRS fish also showed fin erosion in caudal and both pectoral fins. RAS and IPRS fish demonstrated similar survival rates. Conversely, the POND group exhibited significantly lower survival, likely because of adaptability and water quality issues. Blood plasma analysis of POND fish indicated starvation, marked by elevated alanine aminotransferase and lipase levels, supported by non-existing fat reserves. In summary, RAS yielded the best growth and feed efficiency, although it was associated with increased metabolic stress and fin erosion. IPRS showed slower growth but proved cost-effective during the growing season. Traditional pond culture was unsuccessful owing to adaptability in and the water quality of ponds. An economic evaluation revealed that production costs per pikeperch juvenile were significantly lower in the IPRS compared with that in the RAS, thereby compensating for slower growth.